Changes in microstructure, solidification path and hydrogen permeability of Nb–Hf–Co alloy by adjusting Hf/Co ratio. (21st January 2016) - Yan, Erhu; Sun, Lixian; Xu, Fen; Xu, Daming; Qiu, Shujun; Xiang, Cuili; Zhang, Huanzhi; Sun, Yixin
Abstract: The effect of Hf/Co ratio on microstructure, solidification path and hydrogen permeability of as-cast Nb40 Hf30+x Co30−x and Nb35 Hf32.5+x Co32.5−x (x = −2, 0, 2, 4) alloys is investigated. The above two series of alloys mainly consist of the primary BCC-(Nb, Hf) and the eutectic BCC-(Nb, Hf) + Bf -HfCo phases, while Nb40 Hf34 Co26 alloy additionally contains small fractions of the Hf2 Co phase that results from a ternary eutectic reaction. Increase of Hf/Co ratio induces higher fraction of primary BCC-(Nb, Hf) and Hf2 Co phases. Two kinds of solidification paths are found in this two series of alloys, particularly [L→BCC-(Nb, Hf)]→[L→BCC-(Nb, Hf) + Bf -HfCo] and [L→BCC-(Nb, Hf)]→[L→BCC-(Nb, Hf)+Bf -HfCo]→[L→BCC-(Nb, Hf) + Bf -HfCo + Hf2 Co]. The permeability increases with increasing Hf/Co ratio and increasing volume fraction of the primary BCC-(Nb, Hf) phase. Nb40 Hf32 Co28 (x = 2) exhibits a high hydrogen permeability of 5.21 × 10 −8 mol H2 m −1 s −1 Pa −1/2 at 673 K and excellent durability in hydrogen permeation (∼72 h), which becomes superior to that of the Nb40 Hf30 Co30 previously reported to be the best in the Nb–Hf–Co alloy series. The present work demonstrates that the hydrogen permeability of this alloy series can be optimized by appropriately adjusting the Hf/Co ratio for a given niobium content. Highlights: The microstructure and permeability can be optimized by adjusting the Hf/Co ratio. Increase of Hf/Co ratio induces more primary phase and less eutectic. Larger Hf/Co ratio induces higher hydrogen solubility, diffusivity and permeability. Nb40 Hf32 Co28 shows the highest permeability of 5.21 × 10 −8 mol H2 m −1 s −1 Pa −0.5 . Nb40 Hf32 Co28 is promising to make high-performance membranes for H2 separation.